2002
DOI: 10.1139/f02-001
|View full text |Cite
|
Sign up to set email alerts
|

Shifting gears: enzymatic evidence for the energetic advantage of switching diet in wild-living fish

Abstract: Large variations in the activity and scaling patterns of enzymes involved in anaerobic metabolism exist and appear to be related to species differences in the locomotory habits of fish. Here, we show how the scaling of muscle lactate dehydrogenase (LDH) activity is highly variable in fish, not only among species, but also among populations of yellow perch (Perca flavescens) and lake trout (Salvelinus namaycush) exhibiting large differences in the scaling of fish activity costs. These differences in LDH scaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
88
2
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 35 publications
7
88
2
4
Order By: Relevance
“…Other considerations include availability of prey and the subsequent costs associated with pursuit, capture, handling and digestion. In fish, diet shifts with increasing body size are thought to reflect the limiting factor of gap size and the increasing foraging cost of consuming relatively smaller prey (Sherwood et al 2002). That is, a shift in diet is made when the costs outweigh the benefits of feeding on a particular prey or prey-size class (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other considerations include availability of prey and the subsequent costs associated with pursuit, capture, handling and digestion. In fish, diet shifts with increasing body size are thought to reflect the limiting factor of gap size and the increasing foraging cost of consuming relatively smaller prey (Sherwood et al 2002). That is, a shift in diet is made when the costs outweigh the benefits of feeding on a particular prey or prey-size class (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…That is, a shift in diet is made when the costs outweigh the benefits of feeding on a particular prey or prey-size class (e.g. Jones et al 1994, Sherwood et al 2002. This, in turn, leads to lower energetic demands, with respect to minimizing time and activity costs spent in burst swimming and pursuit of prey (Sherwood et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A de-pauperate prey field can limit or prevent the ontogenetic diet shifts that a predator typically exhibits as it increases in body size and can result in slower individual growth rates Sherwood et al 2002); preliminary work suggests that the diet of Provoking bass is lacking in large-sized prey (Orendorff 1983). Water temperatures are also important in determining individual growth in bass and should be examined as a possible driver of divergence .…”
Section: Introductionmentioning
confidence: 99%
“…However, when examining Kadj for all regions together, I did find a general decrease in feeding, and a shift in diet from predominantly squid and fish to crabs, occurred between 28-36 cm total length, when a decrease in Kadj was also observed. Sherwood et al (2002) found that prey switching often occurs when condition starts to decline, suggesting that these diet changes may be necessary to overcome energetic bottlenecks.…”
Section: Discussionmentioning
confidence: 99%